Is there an association between hot weather and poor mental health outcomes? A systematic review and meta-analysis. (August 2021) - Liu, Jingwen; Varghese, Blesson M.; Hansen, Alana; Xiang, Jianjun; Zhang, Ying; Dear, Keith; Gourley, Michelle; Driscoll, Timothy; Morgan, Geoffrey; Capon, Anthony; Bi, Peng
Highlights: Evaluated short-term associations of heat on mental health-related outcomes. A 2.2% increase in mental health-related mortality per 1 °C rise in temperature. A 0.9% increase in mental health-related morbidity per 1 °C rise in temperature. Heatwaves increase the risk of mental health-related outcomes. Higher risks for elderly, and those living in Tropical and Subtropical climates. Abstract: Background: Mental health is an important public health issue globally. A potential link between heat exposure and mental health outcomes has been recognised in the scientific literature; however, the associations between heat exposure (both high ambient temperatures and heatwaves) and mental health-related mortality and morbidity vary between studies and locations. Objective: To fill gaps in knowledge, this systematic review aims to summarize the epidemiological evidence and investigate the quantitative effects of high ambient temperatures and heatwaves on mental health-related mortality and morbidity outcomes, while exploring sources of heterogeneity. Methods: A systematic search of peer-reviewed epidemiological studies on heat exposure and mental health outcomes published between January 1990 and November 2020 was conducted using five databases (PubMed, Embase, Scopus, Web of Science and PsycINFO). We included studies that examined the association between high ambient temperatures and/or heatwaves and mental health-related mortality and morbidity (e.g. hospital admissions and emergency department visits) in the general population. A range of mental health conditions were defined using ICD-10 classifications. We performed random effects meta-analysis to summarize the relative risks (RRs) in mental health outcomes per 1 °C increase in temperature, and under different heatwaves definitions. We further evaluated whether variables such as age, sex, socioeconomic status, and climate zone may explain the observed heterogeneity. Results: The keyword search yielded 4560 citations from which we identified 53 high temperatures/heatwaves studies that comprised over 1.7 million mental health-related mortality and 1.9 million morbidity cases in total. Our findings suggest associations between heat exposures and a range of mental health-related outcomes. Regarding high temperatures, our meta-analysis of study findings showed that for each 1 °C increase in temperature, the mental health-related mortality and morbidity increased with a RR of 1.022 (95%CI: 1.015–1.029) and 1.009 (95%CI: 1.007–1.015), respectively. The greatest mortality risk was attributed to substance-related mental disorders (RR, 1.046; 95%CI: 0.991–1.101), followed by organic mental disorders (RR, 1.033; 95%CI: 1.020–1.046). A 1 °C temperature rise was also associated with a significant increase in morbidity such as mood disorders, organic mental disorders, schizophrenia, neurotic and anxiety disorders. Findings suggest evidence of vulnerability for populations living in tropical and subtropical climate zones, and for people aged more than 65 years. There were significant moderate and high heterogeneities between effect estimates in overall mortality and morbidity categories, respectively. Lower heterogeneity was noted in some subgroups. The magnitude of the effect estimates for heatwaves varied depending on definitions used. The highest effect estimates for mental health-related morbidity was observed when heatwaves were defined as "mean temperature ≥90th percentile for ≥3 days" (RR, 1.753; 95%CI: 0.567–5.421), and a significant effect was also observed when the definition was "mean temperature ≥95th percentile for ≥3 days", with a RR of 1.064 (95%CI: 1.006–1.123). Conclusions: Our findings support the hypothesis of a positive association between elevated ambient temperatures and/or heatwaves and adverse mental health outcomes. This problem will likely increase with a warming climate, especially in the context of climate change. Further high-quality studies are needed to identify modifying factors of heat impacts.